Who Should Be Considered for Islet Transplantation Alone? - Othonos, Nantia (Curr Diab Rep, 2017)
PURPOSE OF REVIEW: Episodic hypoglycemia is an almost inevitable consequence of exogenous insulin treatment of type 1 diabetes, and in up to 30% of patients, this can lead to impaired awareness of hypoglycemia. This predisposes to recurrent severe hypoglycemia and has a huge impact on quality of life. Although many patients can get resolution of severe hypoglycemia through novel education and technology, some patients continue to have ongoing life-threatening hypoglycemia. Islet transplantation offers an alternative therapeutic option for these patients, in whom these conventional approaches have been unsuccessful. This review discusses the selection process of identifying suitable candidates based on recent clinical data. RECENT FINDINGS: Results from studies of islet transplantation suggest the optimal recipient characteristics for successful islet transplantation include age >35 years, insulin requirements <1.0/kg, and weight >85 kg. SUMMARY: Islet transplantation can completely resolve hypoglycemia and near-normalize glucose levels, achieving insulin independence for a limited period of time in up to 40% of patients. The selection of appropriate candidates, optimizing donor selection, the use of an optimized protocol for islet cell extraction, and immunosuppression therapy have been proved to be the key criteria for a favorable outcome in islet transplantation.